Improved DEMATEL methodology for effective safety management decision-making. (July 2020) - Yazdi, Mohammad; Khan, Faisal; Abbassi, Rouzbeh; Rusli, Risza
Highlights: A systematic approach is proposed to build causal decision-making models. The proposed approach combined multi-criteria decision making tools and a Bayesian Network. The resulting models are based on knowledge elicited from multiple experts. The proposed approach is applied to a safety management system case study. The model's advantages is evaluated with different available approaches. Abstract: Decision-making is a critical step in safety and risk analysis. Decision-making is conducted according to the different sources of information often elicited from filed matter and subject matter experts. Many team-based decision-making methods are developed to identify hazards, determine intervention actions, and to prioritize the efforts to reduce the risk in given conditions. However, the majority of decision-making methods are based on idealistic assumptions such as risk contributing factor in a complex system and independency between the factors. In reality, there is strong interaction among the risk factors and also among the sources of information used in decision-making procedure. There is a requirement to use a decision-making framework that captures the dependency of the risk factors and the source of information. This is achieved by integrating DEMATEL (decision-making trial and evaluation laboratory) methodology with Best-Worst method (BWM) and Bayesian network (BN). The integration is considered at two different stages in the DEMATEL methodology. Application of the integrated DEMATEL is illustrated by adopting a case study of safety management in the high-tech industry.